2010
DOI: 10.1007/s11027-010-9237-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing risk of and adaptation to sea-level rise in the European Union: an application of DIVA

Abstract: This paper applies the DIVA model to assess the risk of and adaptation to sealevel rise for the European Union in the 21st century under the A2 and B1 scenarios of the Intergovernmental Panel on Climate Change. For each scenario, impacts are estimated without and with adaptation in the form of increasing dike heights and nourishing beaches. Before 2050, the level of impacts is primarily determined by socio-economic development. In 2100 and assuming no adaptation, 780×10 3 people/year are estimated to be affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 28 publications
2
102
0
2
Order By: Relevance
“…During extreme conditions, most hydro-and morphodynamic processes are accelerated, with the most dramatic implication being the fact that the water level can exceed the height of natural (e.g., dunes, cliffs) or anthropic barriers (e.g., sea walls, dykes), and reach areas not prepared to interact with the water element, often with catastrophic consequences. This is the reason that marine storms are considered as extreme when they coincide with coastal inundation, and inundation maps are a crucial element for several coastal management and engineering practices, i.e., post-evaluation of extreme events, coastal planning, definition of set-back lines (Ferreira et al, 2006), and evaluation of adaptation options (Cooper and Pile, 2014;Hinkel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During extreme conditions, most hydro-and morphodynamic processes are accelerated, with the most dramatic implication being the fact that the water level can exceed the height of natural (e.g., dunes, cliffs) or anthropic barriers (e.g., sea walls, dykes), and reach areas not prepared to interact with the water element, often with catastrophic consequences. This is the reason that marine storms are considered as extreme when they coincide with coastal inundation, and inundation maps are a crucial element for several coastal management and engineering practices, i.e., post-evaluation of extreme events, coastal planning, definition of set-back lines (Ferreira et al, 2006), and evaluation of adaptation options (Cooper and Pile, 2014;Hinkel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The static inundation approach ("bath tub") considers all the areas with elevation lower than the forcing water level as flooded, comes with low computational costs and can easily be performed in GIS (geographic information system) environments (Seenath et al, 2016); for that reason it has been extensively used for studies of different scales (Hinkel et al, 2010(Hinkel et al, , 2014Vousdoukas et al, 2012c). However, given the high complexity of coastal flooding processes, several recent studies showed that the static approach results in substantial overestimation of the flood extent compared to dedicated hydraulic models, especially in flatter terrains (Breilh et al, 2013;Gallien, 2016;Ramirez et al, 2016;Seenath et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A number of climate change impact studies at the European level have been achieved, usually for a single specific climate or weather hazard, such as river floods (Rojas et al 2012;Alfieri et al 2015), coastal floods (Nicholls and Klein 2005;Hinkel et al 2010), heat waves (Fischer and Schär 2010;Russo et al 2015;Christidis et al 2015), streamflow droughts (Lehner et al 2006;Forzieri et al 2014), windstorms (Nikulin et al 2011;Outten and Esau 2013) and wildfires (Bedia et al 2013;Migliavacca et al 2013a). The study of multiple hazards poses two major challenges: (1) hazards are not directly comparable as their processes and describing metrics differ; and (2) hazards can interact triggering cascade effects and coupled dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The DIVA tool (Vafeidis et al 2008;Hinkel and Klein 2009;Hinkel et al 2010) was obtained from Jochen Hinkel, maintaining the tool for the DINAS-COAST consortium. DIVA combines a global database of the world's coast broken down in coastal segments of variable length with a world climate and socio-economic model.…”
Section: Methodsmentioning
confidence: 99%